Social media experiences of solo leisure travelers during the travel process: A phenomenological study - Ahmet Elnur; Hakkı Akgün (Heliyon)
The rise of solo travel has become a significant trend in the leisure sphere; nonetheless, there is limited understanding of how solo travelers utilize social media throughout their travel process. This lack of insight represents a research problem, as it hinders the ability to enhance solo travel experiences through social media engagement. Addressing this gap, this study investigates the specific ways in which solo leisure travelers experience and engage with social media during their journeys. Using a qualitative phenomenological approach, in-depth interviews were conducted with 18 solo travelers to explore the impact of social media on their travel experiences. Analysis revealed five key themes: sharing experiences, seeking information, documenting memories, minimal use of social media, and feelings of loneliness and connection. The findings demonstrate that social media plays a multifaceted role in shaping solo travel experiences, serving as a tool for information gathering, memory preservation, and maintaining social connections. However, an emerging trend of minimal social media use reflects a desire among some travelers for greater mindfulness and immersion in the present moment. This study contributes to a deeper understanding of the complex relationship between social media use and solo travel, highlighting implications for travelers and the tourism industry in catering to the evolving needs of independent travelers in the digital age.